KELOMPOK MASYARAKAT DESA PIPA PUTIH, BERTANAM KELOR DAN MENIRAN SERTA MANFAATNYA UNTUK KESEHATAN MASA PANDEMI COVID-19 - Sonlimar Mangunsong; fadly fadly; Vera Astuti (ABDIKEMAS: Jurnal Pengabdian Kepada Masyarakat, 2021)
Empowerment community has been carried out through planting Kelor and Meniran to be used as health food during the Covid 19 pandemic. The implementation was carried out in Village of Pipa Putih, RT 6, Ogan Ilir, South Sumatera. It is 30 km from the city of Palembang, a collaboration partner with the Palembang Health Polytechnic. Using two plots of land owned by the residents village of Pipa Putih, the implementing groups are PKK Cadres and the Office Pipa Putih . Provide farming equipment and garden fences. Provide Kelor dan Meniran seeds obtained from nurseries, then given to partner groups to be planted and maintained for 2 months Monitoring was carried out every week on the activities of growing Kelor dan Meniran. The results obtained are Kelor dan Meniran plants can be harvested after 1.5 months of cultivation. The harvest can be processed into healthy food in the form of agar pudding, bandrek, cendol, chips and noodles made from Kelor dan Meniran. Evaluation took from the increase in knowledge, attitudes and behaviors that have been realized in community service planting Kelor dan Meniran. The theme of this activity was followed up by making the superior ready-to-eat product of cadre levels PKK Pipa Putih and at the coverage village.